Trajectories in the care of homeless individuals with tuberculosis diagnosis: an integrative review - Jorge Almeida Meirelles, Richardson (2024)
This study reviewed research from 2013 to 2023 on the healthcare trajectories of tuberculosis (TB) among people experiencing homelessness (PEH), analyzing its impact on treatment. Out of 87 studies found, 10 were selected after screening, all published between 2015 and 2023. These studies emphasized the care practices and challenges faced by PEH, highlighting social invisibility, structural barriers, and stigma. Most used qualitative methodologies, exploring the services provided by the Street Clinic teams (CnaR) in various regions of Brazil. High alcohol and drug use among PEH was a complicating factor in TB treatment. Factors such as lack of stable housing, food insecurity, and prejudice also negatively influenced treatment adherence. However, integrated approaches that addressed the social and health needs of PEH proved effective. The CnaR teams played a crucial role in offering comprehensive and personalized care, strengthening the bond of trust. Treatment adherence improved with continuous and tailored interventions. The research underscores the need for public policies that integrate medical care and support, aligned with the specific demands of PEH.